EDUCATIONAL PHRAZEOGRAPHY AS A SPECIAL DEPARTMENT OF LEXICOGRAPHY (Scientific journal of the Fergana State University, 2023)
This reveals phraseological dictionaries, including the selection of educational phraseological dictionaries, linguistic aspects of compiling an educational phraseological dictionary, Uzbek phraseographic dictionary, the stages of development of Uzbek educational phraseography, the history of dictionary science, multilingual dictionaries and the dictionary building.